Towards Large Language Models for Everyone: Instruction Following, Knowledge Retrieval and Multilingualism - Lin, Xi (My University, 2024)
Large language models (LLMs) have significantly advanced the field of Natural Language Processing and demonstrated the potential to fuel a variety of AI applications. Nonetheless, building them in a way that maximally benefits the very wide range of everyday use cases is challenging. Firstly, LLMs are pre-trained with the next-token prediction objective, which does not align well with specific user requests. Secondly, LLMs suffer from knowledge cut-off and tend to hallucinate about long-tail facts. Lastly, popular LLMs are trained on almost exclusively English text, making it difficult for non-English speakers to adopt them. This thesis presents methodologies addressing all three challenges. We begin by studying the Instruction Meta-Learning (IML) approach, enabling LLMs to perform an array of tasks by fine-tuning them over pairs of natural language instructions and responses. Our study highlights the efficacy of scaling IML along three axes: fine-tuning task diversity, language diversity and model parameters. Next, we propose integrating LLMs with an external data store during IML (retrieval-augmented dual instruction tuning, RA-DIT). RA-DIT significantly improves LLM performance in scenarios that require access to large, external knowledge sources (e.g., answering information-seeking questions). Finally, we introduce a family of cross-lingual generative language models (XGLMs) pre-trained on a multilingual corpus exhibiting a heavy-tailed distribution. XGLMs demonstrate enhanced cross-lingual capabilities and few-shot generalization across medium- and low-resource languages. Together, these research strands provide core strategies for advancing the boundaries of LLM capabilities and paving the way towards real-world deployment.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: foundation model; knowledge retrieval; large language model; multilingualism; Computer science; Artificial intelligence; Computer science and engineering